Imposed volunteering: Gender and caring responsibilities during the COVID-19 lockdown. Issue 1 (January 2022) - Andersen, Ditte; Toubøl, Jonas; Kirkegaard, Sine; Bang Carlsen, Hjalmar
This article contributes to the sociology of care-relational justice by identifying, conceptualising and unpacking 'imposed volunteering' as a mechanism that shapes societal caring arrangements. Contemporary societies allocate care work disproportionately to women, ethnic minorities and working-class citizens, which exacerbates social inequalities. Distribution of caring responsibilities is a political question but often not recognised as such, because it is deeply immersed in everyday routines. Our study uses the context of the COVID-19 pandemic to dissect the distribution mechanisms that became unusually palpable when the lockdown of public welfare provision in Denmark relocated some forms of care work from professionals to volunteers. With the term imposed volunteering, we conceptualise the feeling of being coerced into taking on new caring responsibilities, which some women – and men – experienced during the lockdown. Drawing on a national, representative survey, we document that, compared to men, women carried out significantly more voluntary care work and organised voluntary work through informal personal networks rather than through formal civil society organisations to a significantly higher degree. We unpack the experience of imposed volunteering as it unfolded during the lockdown through qualitative case studies, and clarify how relational and institutional factors, such as gendered expectations and the sense of personal obligation, imposed volunteering. Our study illuminates the importance of public care, reciprocal caring relationships and care for carers, and demonstrates why the mobilisation of care work volunteers must take gendered implications into account if it is to be consistent with democratic commitments to justice, equality and freedom for all.